Juridical Analysis of the Handling of Terrorism Crime - Dhanu Hariwijaya; Herry Irfanto; Fadhli Ghifari SP; Agus Dimyati; Anom Sutrisno (Pusat Publikasi Nusantara, 2024)
The research aims to study the police's countermeasures for dealing with acts of terrorism in Cirebon Regency, Indonesia. This study uses a normative juridical approach, focusing on analyzing legal regulations and their application in practice. The study identifies that although laws and regulations such as Law Number 5 of 2018 provide a strong legal basis, implementation still faces challenges related to the effectiveness of coordination between law enforcement officials and intelligence agencies. The findings of this study also contribute to the development of law and public policy in Indonesia by providing a solid academic foundation to support necessary regulatory changes or adjustments. The results of this analysis can help policymakers in formulating more responsive and adaptive strategies in dealing with the threat of terrorist, so as to create a stronger legal system and be able to protect society more comprehensively.